Market Levy Contribution to Local Revenue for the City of Bukittinggi in 2018-2022 - Cindy, Cindy; Lukman, Lukman; Weriantoni, Weriantoni; Saibah, Bintang Rizky Abdullah Majo (Jurnal Ekonomi Balance, 2023)
This research is motivated by the importance of market fees for increasing local revenue (PAD). And also for the last 10 years, in 2022 it archieved its highest income of 114 billion. One of the government’s efforts to increase revenue is by collecting market fees. The purpose of this research is to find out how big the contribution of market levies is to Local Own Revenue and find out the development of market levies in city of Bukittinggi. The type of research used in this study is a quantitative approach. The type of data used is secondary data. Meanwhile, the research location is the City of Bukittinggi Revenue Section Finance Agency and the Office of Cooperatives, SMEs and Trade of the City of Bukittinggi. The contribution of market levies to the Regional Original Revenue of the City of Bukittinggi in 2018-2022 includes the very low contribution criteria, where the contribution is less than 10%. With the highest contribution rate of 1.72% which occurred in 2019 and the lowest contribution in 2020 with a contribution of 1.06%. In addition, the prospect of receiving market levies is a trend (development) that tends to be positive. In the next year, namely 2023, the receipt of market levies has the potential to increase, but the increase will not to be sharp increase, thus affecting the trend of market levies in recent years will come.